Screening of 439 Pesticide Residues in Fruits and Vegetables by Gas Chromatography-Quadrupole-Time-of-Flight Mass Spectrometry Based on TOF Accurate Mass Database and Q-TOF Spectrum Library. (23rd November 2019) - Li, Jian-Xun; Li, Xiao-Ying; Chang, Qiao-Ying; Li, Yan; Jin, Ling-He; Pang, Guo-Fang; Fan, Chun-Lin
Abstract: Because of its unique characteristics of accurate mass full-spectrum acquisition, high resolution, and fast acquisition rates, GC-quadrupole-time-of-flight MS (GC-Q-TOF/MS) has become a powerful tool for pesticide residue analysis. In this study, a TOF accurate mass database and Q-TOF spectrum library of 439 pesticides were established, and the parameters of the TOF database were optimized. Through solid-phase extraction (SPE), whereby pesticides are extracted from fruit and vegetable substrates by using 40 mL 1% acetic acid in acetonitrile (v/v), purified by the Carbon/NH2 SPE cartridge, and finally detected by GC-Q-TOF/MS, the rapid analysis of 439 pesticides in fruits and vegetables can be achieved. The methodology verification results show that more than 70 and 91% of pesticides, spiked in fruits and vegetables with concentrations of 10 and 100 μg/kg, respectively, saw recoveries that conform to the European Commission's criterion of between 70 and 120% with RSD ≤20%. Eighty-one percent of pesticides have screening detection limits lower than 10 μg/kg, which makes this a reliable analysis technology for the monitoring of pesticide residues in fruits and vegetables. This technology was further validated for its characteristics of high precision, high speed, and high throughput through successful detection of 9817 samples during 2013–2015.